2016
DOI: 10.1007/s00181-015-1037-5
|View full text |Cite|
|
Sign up to set email alerts
|

Real estate returns predictability revisited: novel evidence from the US REITs market

Abstract: In this paper we examine the real estate returns predictability employing US Real Estate Investment Trusts (REITs) and a set of possible predictors for the period January 1991 to December 2014. To this end we employ several forecasting models to test for REITs predictability under a flexible framework that captures parameter instability. Apart from the traditional factors examined in relevant studies, we also account for a series of sentiment and uncertainty indicators that may be significant predictors of REI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 42 publications
(42 reference statements)
2
17
0
Order By: Relevance
“…However, just like any other security, as the financial integration goes up, the importance of cross-market interactions also become increasingly significant for the investors. Furthermore, the real estate market having played a significant role during the most recent global financial crisis, and the REIT market being a good proxy for the overall real estate sector (Akinsomi et al, 2016), policy makers also have a vested interest in understanding the drivers of these markets (Gupta and Marfatia, 2018;Gupta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, just like any other security, as the financial integration goes up, the importance of cross-market interactions also become increasingly significant for the investors. Furthermore, the real estate market having played a significant role during the most recent global financial crisis, and the REIT market being a good proxy for the overall real estate sector (Akinsomi et al, 2016), policy makers also have a vested interest in understanding the drivers of these markets (Gupta and Marfatia, 2018;Gupta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2 Moreover, the role of US monetary policy on the international platform has also evolved in the last 30 years (Hausman and Wongswan 2011;Kishor and Marfatia 2013;Marfatia 2014). It is no surprise then that studies find that factors that explain the movements in the REIT market differ greatly in the turbulent times as compared to normal periods (Ghysels et al 2013;Akinsomi et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…They found that the effect of US monetary policy on global REITs varied widely across time and between countries. Earlier work by (Xu and Yang 2011) using seemingly unrelated regressions (SUR) found that REIT returns for 18 developed countries responded positively to unexpected cuts in the federal funds rate, as well as downside surprises to the future path of federal fund rate (also see Ghysels et al 2013;Akinsomi et al 2016).…”
Section: Introductionmentioning
confidence: 98%
“…The results indicated that REITs were generally efficient during this time period. More recently, Akinsomi, Aye, Babalos, Economou, and Gupta (2016) show that economic, monetary and sentiment indicators help in better predicting REIT returns.…”
Section: Literature Reviewmentioning
confidence: 99%